2005
DOI: 10.1016/j.jvs.2005.01.047
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerotic risk factor control in patients with peripheral arterial disease

Abstract: Despite national consensus of PAD as a CAD equivalent, patients are currently undertreated with regard to atherosclerotic risk factor modification. Until broader recognition of this disease process exists, vascular surgeons must continue to champion medical as well as surgical treatments for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
33
0
11

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 50 publications
(38 reference statements)
2
33
0
11
Order By: Relevance
“…15,[21][22][23][24][25][26][27][28][29][30] Even in ideal conditions, the success rates in reaching national targets are dismal. In a study of a socioeconomically homogeneous, multiethnic, well-educated population with comprehensive medical benefits, Ͼ80% failed to achieve blood pressure control despite full access to and active participation in the community's medical care system.…”
Section: Discussionmentioning
confidence: 99%
“…15,[21][22][23][24][25][26][27][28][29][30] Even in ideal conditions, the success rates in reaching national targets are dismal. In a study of a socioeconomically homogeneous, multiethnic, well-educated population with comprehensive medical benefits, Ͼ80% failed to achieve blood pressure control despite full access to and active participation in the community's medical care system.…”
Section: Discussionmentioning
confidence: 99%
“…2 The presence of major cardiovascular risk factors leads to an increased prevalence of coronary artery disease in PAD patients, as well as an increase in the incidence of new coronary events. 3 In PAD patients, all-cause mortality was determined to be 3.1 times higher than in non-PAD patients, and death because of coronary artery disease was 6.6 times higher. 4 Investigators reported on a range of the incidence of normal coronary arteries and coronary arteries with lesions in PAD patients, based on angiographic assessments.…”
mentioning
confidence: 91%
“…4,6 Despite these recommendations, as well as numerous studies showing the benefit of lipid-lowering treatment in PAD patients, optimal medical management remains inadequate. 5,[7][8][9][10][11] Progression of PAD to critical limb ischemia (CLI) is seen in 1% of affected patients per year, but patients who progress to this level may have a 10-fold to 15-fold increased risk of cardiovascular death. 2 CLI has traditionally been treated by open intervention, but advances in endovascular techniques have altered the treatment algorithm.…”
mentioning
confidence: 99%
“…[12][13][14][15][16] This shift toward less invasive interventions is aimed at reducing morbidity and mortality, but adjunct medical treatments that may further reduce the risk for cardiovascular death continue to be underutilized. [9][10] Despite the growing amount of data documenting the benefit of statins in the perioperative period after major vascular operations as well as in patients receiving conservative management, little is known of their clinical effect in patients undergoing peripheral endovascular treatment. [17][18][19][20] The purpose of this study was to review the effects of statin therapy in endovascular treatment of patients with CLI.…”
mentioning
confidence: 99%